Urinary Bladder Carcinoma: Impact of Smoking, Age and its Clinico-Pathological Spectrum - Joshi, HN; Makaju, R; Karmacharya, A; Kamracharya, RM; Shrestha, B; Shrestha, R; de Jong, IJ; Shrestha, RKM (Kathmandu University Medical Journal, 2015)
Background Urinary bladder carcinoma is common urological malignancy. Although epidemiological evidence favors role of occupational exposure to chemical carcinogen as the aetiological factor of bladder carcinoma, many cases arise with no obvious occupational exposure to chemical carcinogen. Tobacco and cigarette smoking is common in both rural and urban areas of Nepal.Objective The objective of this study was to determine the impact of smoking and age in urinary bladder carcinoma with related clinicopathological correlations.Method A total of 56 (44 males and 12 females) cases of urinary bladder cancer treated at Dhulikhel Hospital, Kathmandu University Teaching Hospital during time period of January 2004 to December 2013 were included in the study. Data of patients with Urinary bladder cancer were obtained from hospital records and evaluated for age, sex, history of smoking, clinical presentations, cystoscopic findings and histopathological characteristics.Results Out of 56 cases, 51 (91.1%) of the patients had hematuria. History of smoking was found in 44 patients. Smoking was found much higher in males (88%) than females (41.66%). Transitional cell carcinoma (TCC) was the most common histological variety, which was seen in 51 (91.07%) patients. The significant impact of smoking was found in terms of grade of TCC.Conclusion The incidence of bladder carcinoma is higher in male and TCC is the most common variety of Urinary bladder malignancy. History of smoking correlated with grade.Kathmandu Univ Med J 2013; 11(4): 292-295